Fully automated light transmission aggregometry on a disc for platelet function tests. Issue 23 (9th November 2021) - Kim, Chi-Ju; Kim, Jungmin; Sabaté del Río, Jonathan; Ki, Dong Yeob; Kim, Junyoung; Cho, Yoon-Kyoung
Abstract : We report a fully automated light transmission aggregometry (LTA) assay on a disc that can provide point-of-care testing to assess the function of platelets. Abstract : Platelet function tests, a group of assays that measure the ability of platelets to aggregate and promote clotting in a sample of blood, are performed in various medical fields to assess inherited platelet function disorders and monitor antiplatelet therapies. Light transmission aggregometry (LTA) is considered the gold standard for platelet function assessment. However, the lack of a standardized protocol is a major drawback when applied at the point of care. Moreover, it is a time-consuming and labor-intensive assay that requires a large volume of blood. Here, we describe the design, fabrication, and operation of a centrifugal microfluidic disc that can perform a fully automated LTA assay from a small volume of a whole blood sample (<1 mL), achieving highly reproducible results (3.2% coefficient of variation) within a short period (<25 min). The assays performed with this device yield more precise and accurate results than traditional LTA because of the automation of the reaction steps, minimal human operation, robust detection strategy via the distinctive structure of the microfluidic chamber, and quick analysis that minimizes the adverse effects of platelet instability.